ENHANCING SUSTAINABLE FUTURE: HARNESSING HARMONIOUS YOUTH ENERGIES" (Ustozlar uchun, 2024)
Abstract: This study investigates the pathways through which harmonious youth energies contribute to sustainable development goals. Drawing from a synthesis of literature and empirical analysis, it uncovers the transformative potential of engaging young people in sustainable initiatives. The findings highlight the importance of creating conducive environments, providing education and resources, and fostering inclusive participation to leverage the positive impact of youth energies on sustainable futures.